Mixing Performance of a Planar Asymmetric Contraction-and-Expansion Micromixer - Daigo Natsuhara; Ryogo Saito; Shunya Okamoto; Moeto Nagai; Takayuki Shibata (Micromachines, 2022)
Micromixers are one of the critical components in microfluidic devices. They significantly affect the efficiency and sensitivity of microfluidics-based lab-on-a-chip systems. This study introduces an efficient micromixer with a simple geometrical feature that enables easy incorporation in a microchannel network without compromising the original design of microfluidic devices. The study proposes a newly designed planar passive micromixer, termed a planar asymmetric contraction-and-expansion (P-ACE) micromixer, with asymmetric vertical obstacle structures. Numerical simulation and experimental investigation revealed that the optimally designed P-ACE micromixer exhibited a high mixing efficiency of 80% or more within a microchannel length of 10 mm over a wide range of Reynolds numbers (0.13 ≤ Re ≤ 13), eventually attaining approximately 90% mixing efficiency within a 20 mm microchannel length. The highly asymmetric geometric features of the P-ACE micromixers enhance mixing because of their synergistic effects. The flow velocities and directions of the two fluids change differently while alternately crossing the longitudinal centerline of the microchannel, with the obstacle structures asymmetrically arranged on both sidewalls of the rectangular microchannel. This flow behavior increases the interfacial contact area between the two fluids, thus promoting effective mixing in the P-ACE micromixer. Further, the pressure drops in the P-ACE micromixers were experimentally investigated and compared with those in a serpentine micromixer with a perfectly symmetric mixing unit.